Curcumin, an active component of turmeric: biological activities, nutritional aspects, immunological, bioavailability, and human health benefits - a comprehensive review - El-Saadony, Mohamed T.; Saad, Ahmed M.; Mohammed, Dina Mostafa; Alkafaas, Samar Sami; Ghosh, Soumya; Negm, Shaimaa H.; Salem, Heba M.; Fahmy, Mohamed A.; Mosa, Walid F. A.; Ibrahim, Essam H.; AbuQamar, Synan F.; El-Tarabily, Khaled A. (Frontiers in Immunology, 2025)
Curcumin (1,7-bis-(4-hydroxy-3-methoxyphenyl)-hepta-1,6-diene-3,5-dione) is a naturally occurring polyphenol molecule. It is lipophilic and has demonstrated in vitro and in vivo therapeutic effects through multiple pathways. Extensive studies on its pharmacological properties have shown its anti-inflammatory, antioxidant, antinociceptive, antimicrobial, antiparasitic, antimalarial, and wound-healing properties. However, its limited bioavailability in humans due to poor intestinal absorption, rapid metabolism, and rapid systemic elimination remains a significant challenge. Various curcumin formulations have been developed to address this limitation. This article reviews current studies on the biological and pharmacological properties of curcumin. It also examines methods for curcumin isolation, including pressurized fluid extraction, Soxhlet extraction, enzyme-assisted extraction, and microwave extraction. Furthermore, analytical methods for the identification and quantification of curcumin in diverse matrices, as well as procedures for formulating curcumin, will also be addressed. This review consolidates recent studies on curcumin’s chemical, bioactive, and pharmacological properties. It also highlights significant knowledge gaps, indicating the need for future research to elucidate curcumin’s mechanism of action, safety, efficacy, and therapeutic potential for treating various human and animal diseases.